PENGARUH KEPEMILIKAN MANAJERIAL DAN KEPEMILIKAN INSTITUSIONAL TERHADAP NILAI PERUSAHAAN PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BEI - neni marlina br prba; Syahril Effendi (JURNAL AKUNTANSI BARELANG, 2019)
This study aims to identify, analyze and determine the effect of managerial ownership and institutional ownership partially and simultaneously on the value of the company in manufacturing companies listed on the Indonesia stock exchange. The method used is quantitative. The population in this study are manufacturing companies listed on the Indonesia Stock Exchange (IDX) from 2013 to 2016. The samples used in this study are manufacturing companies that have certain criteria. The sampling method is done by purposive sampling, which is based on certain criteria. The data analysis technique used is the classic assumption test (normality, multicollinearity, heterocedasticity, and autocorrelation), multiple linear regression, t test, F test and coefficient of determination. Based on multiple linear regression analysis of variable managerial ownership and institutional ownership of firm value obtained Y = 1,419 + 0,014 X1 +1,158 X2 + e. From the results of the t test performed, the sig value of the managerial ownership variable is 0.381> 0.05, it can be concluded that the managerial ownership variable (X1) does not have a significant effect on firm value. While the sig value of institutional ownership is 0,000 <0,05, it can be concluded that institutional ownership (X2) has a significant effect on firm value. From the results of the F test or the tests carried out simultaneously, the sig value is 0,000 <0,05, it can be concluded that management ownership (X1) and institutional ownership (X2) together have a significant effect on firm value, while the coefficient of determination obtained Adjusted R Square of 0.201. This means that the ability of managerial ownership and institutional ownership variables in explaining the dependent variable is equal to 20.1% and the remaining 79.9% is explained by other variables not discussed in this study.